Antibacterial Activities of the Extracts and Conessine from Holarrhena Floribunda G. DON. (Apocynaceae) - Patrice, Bogne Kamga (African Networks on Ethnomedicines, 2007)
The methanolic extract and conessine isolated from the stem bark of Holarrhena floribunda (Hf) were tested for their antibacterial activities on Bacillus: Bacillus cereus, Bacillus subtilis, Bacillus megaterium and Bacillus stearothermophilus using the disc diffusion method. Phytochemical analysis of the crude extract and fractions was also conducted. The inhibition parameters of the crude methanol extract and the total alkaloid fraction were determined using the macrodilution method. The results showed that the crude extract, the total alkaloid fraction and conessine exhibited a significant antibacterial effect against all the strains studied. The antibacterial effect of conessine is almost similar to that of chloramphenicol used as reference. The ratio of the minimal bactericidal concentration (MBC) over the minimal inhibitive concentration (MIC) indicates the bactericidal effect of the plant. These results support common use of stem bark of Hf and conessine isolated from Hf in the treatment of some infectious diseases.